2016
DOI: 10.1007/s10876-016-1053-4
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Au Nanoparticles with Chlorambucil for Improved Anticancer Activity

Abstract: Gold nanoparticles (AuNPs) of 30-40 nm in size has been prepared using A. hirsutus leaves extract as reducing agent for Au 3? ions under microwave irradiation from 60 to 360 s. These biocapped AuNPs were effectively conjugated with activated folic acid (FA, receptor) and chlorambucil (CHL, anticancer drug) molecules. The formation of AuNPs-FA-CHL was confirmed from different characterization techniques such as XRD, UV-Visible spectra, FT-IR and TEM images. The anticancer activity of these bioconjugated AuNPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In contrast, irradiating (656 nm, 60 J cm −2 ) cancer cells incubated with PEG‐ b ‐P(CPH‐ co ‐RuCHL) micelles significantly decreased the cell viability (Figure b). The EC 50 of polymeric micelles was less than 25 µg mL −1 , which is much lower than that of CHL (150 µg mL −1 ) . Because light irradiation (656 nm, 60 J cm −2 ) on the micelles (100 µL, 200 µg mL −1 ) resulted in 90% conversion of the photoreaction (Figure S20b, Supporting Information), we interpret that the released [Ru(CHLtpy)(biq)(H 2 O)] 2+ from the micelles inhibited cancer cell growth.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, irradiating (656 nm, 60 J cm −2 ) cancer cells incubated with PEG‐ b ‐P(CPH‐ co ‐RuCHL) micelles significantly decreased the cell viability (Figure b). The EC 50 of polymeric micelles was less than 25 µg mL −1 , which is much lower than that of CHL (150 µg mL −1 ) . Because light irradiation (656 nm, 60 J cm −2 ) on the micelles (100 µL, 200 µg mL −1 ) resulted in 90% conversion of the photoreaction (Figure S20b, Supporting Information), we interpret that the released [Ru(CHLtpy)(biq)(H 2 O)] 2+ from the micelles inhibited cancer cell growth.…”
Section: Resultsmentioning
confidence: 92%
“…HeLa cells were incubated with [Ru(CHLtpy)(biq)(H 2 O)](PF 6 ) 2 with a concentration from 1.25 to 50 µg mL −1 for 24 h. Cell viability decreased as the concentration of [Ru(CHLtpy)(biq)(H 2 O)] 2+ increased. The half maximal effective concentration (EC 50 ) of [Ru(CHLtpy)(biq)(H 2 O)] 2+ to HeLa cells was ≈13.7 µg mL −1 , much lower than those of both [Ru(CHLtpy)(biq)(H 2 O)] 2+ (≈30 µg mL −1 , Figure S24, Supporting Information) and CHL (≈150 µg mL −1 ) . The result indicated that the two anticancer moieties had synergistic effects and the conjugate [Ru(CHLtpy)(biq)(H 2 O)] 2+ had improved cytotoxicity toward cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the results show that Hsp-AuNPs were able to particularly stimulate the delivery of hesperidin to cancer cells 29 . Previous studies also reported rapid release of chemotherapeutic drug loaded on AuNPs in acidic conditions when compared to neutral conditions 30,31 .…”
Section: Synthesis Of Hsp-aunpsmentioning
confidence: 83%
“…And subjected to dilution with 800 μL of either physiological (pH 7.4) or acidic (pH 5.04). Incubation of the mixtures was performed at 37 °C for different periods of time (5,15,30,60,120,180,240,1440, and 2880 min). After each period, measurement of the absorbance of the solution was achieved by a UV-VIS spectrophotometer at 286 nm.…”
mentioning
confidence: 99%
“…As shown in Figure S2, the reduction and oxidation of disulfide bonds by GSH and H2O2 disrupted the nanoparticles that induced an increase in size and irregular shape. From the DLS measurements, the mean The conjugation of Hep-Cys with Chl was also confirmed by UV-vis spectrophotometry [30][31][32]. As presented in Figure 3a, Chl was successfully grafted onto the Hep backbone, as shown by the UV absorption peak around 304 nm.…”
Section: Formation Of the Self-assembled Prodrugmentioning
confidence: 77%